Prevalence of postnatal depression and associated factors among HIV-positive women in primary care in Nkangala district, South Africa - K Peltzer; M E Shikwane (AOSIS, 2011)
Background. The prevalence of postpartum depression in South Africa is high, but there is lack of prevalence data on postnatal depression among HIV-infected women. Aim. The aim of this study was to determine the prevalence of depressed mood and associated factors in postnatal HIV-positive women in primary care facilities in Nkangala district, Mpumalanga, South Africa. Methods. This cross-sectional study was carried out on 607 HIV-positive postnatal women in 48 primary health care clinics and community health centres in Nkangala district. Postnatal women were recruited by systematic sampling (every consecutive patient over a period of 2 months). Demographic and other data were obtained from all the women who responded to a questionnaire in the local language on male involvement, HIV test disclosure, delivery and infant profile, infant HIV diagnosis, stigma, discrimination, postnatal depression, attendance of support groups and social support. Results. Overall, 45.1% of women reported a depressed mood in the postnatal period. Depressed mood in a multivariable analysis was significantly associated with internalised stigma (odds ratio (OR) 1.12, 95% confidence interval (CI) 1.05 - 1.19; p=0.000), discrimination experiences (OR 1.22, CI 1.03 - 1.46; p=0.023), lack of social support (OR 0.86, CI 0.74 - 0.99; p=0.037) and having had an STI in the past 12 months (OR 2.22, CI 1.21 - 4.04; p=0.010). There were no statistically significant correlations between the Edinburgh Postnatal Depression Scale (EPDS) scores of the women and age, marital status, level of education, employment status and number of own children. Conclusion. Depressed mood is common among HIV-positive postpartum women. This is significantly associated with lack of social support, stigma and discrimination. Routine screening to identify those currently depressed or at risk of depression should be integrated into postnatal care settings to target those most needing intervention.